Character Education for Teenagers in the Era of Society 5.0 Thomas Lickona's Perspective - Muzawir Munawarsyah; Hujjatul Fakhrurridha; Muqowim Muqowim (LP. Ma'arif Janggan Magetan, 2024)
This research explores the relevance of Thomas Lickona's concept of character education in the context of Era Society 5.0. This research collects and analyses various relevant literature using a qualitative research method with a library research type. The data obtained includes books, articles, and other literature on character education and Era Society 5.0. The results show that Era Society 5.0, which emphasizes collaboration between technology and humans, requires strengthening moral values to ensure technology positively impacts social life. Thomas Lickona identified three main elements in character education: knowing the good, loving the good, and acting the good. These elements emphasize the importance of moral knowledge, moral feelings, and moral behaviour, which are interconnected and need to be applied in daily life. The implementation of character education in Era Society 5.0 must integrate technology with moral values through a comprehensive approach, involve all elements of society, and create a learning environment that supports the development of good character. This research concludes that Lickona's concept of character education is very relevant and can be applied effectively in Era Society 5.0 to form individuals with strong characters who can utilize technology wisely.